TANTANGAN PALESTINE RED CRESCENT SOCIETY (PRCS) DALAM MELINDUNGI KORBAN PERANG PALESTINA PERIODE 2002-2009 - Prameswari, Evany Sofia; Windiani, Reni; Pattipeilohy, Shary Charlotte (Journal of International Relations, 2015)
Protection of war victims is an important issue due to the fact thatthere will always be crimes and violations to the things protected bythe law of war. Israeli military action toward Palestine is not onlyinterfering the security of Palestinians, but also obstructing thedistribution of humanitarian assistance for the victims of war.Established in 1968 and acquired mandate from the Government ofPalestine, Palestine Red Crescent Society (PRCS), as underbow ofInternational Committee of the Red Cross (ICRC), attempts to protectPalestinians as victims of war based on the rules of GenevaConventions 1949. Between 2002 until 2009, there were three militaryactions had been done by Israeli toward Palestine which increased thenumber of Palestinian war victims. This thesis is an explorative typeof research aimed to analyse challenges faced by Palestine RedCrescent Society in protecting Palestinian war victims between 2002until 2009. The result of this research showed that the most affectingchallenge came from external factor, that was the bureaucracy ofIsraeli military.